Pengaturan Kepemilikan Rekam Medis Sebelum dan Sesudah Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan - Syifa Bunga Jingga; Muhammad Faiz Mufidi (UNISBA Press, 2024)
Abstract. The lack of clarity regarding the protection of patients' rights to medical records in Law Number 17 of 2023 concerning Health has created a debate about claiming ownership of medical records between patients and health service facilities. This research compares the regulation of ownership of medical records before and after Law Number 17 of 2023 concerning Health and international laws such as the New Hampshire Statute and HIPAA. This research was conducted with the aim of knowing and analyzing ownership of medical records according to Law Number 29 of 2004 and Law Number 17 of 2023 concerning health with the New Hampshire Statute, as well as knowing the legal consequences following the enactment of Law Number 17 of 2023 concerning Health on protecting the rights of patients or families regarding the contents of medical records. The research analysis method used in this research is a qualitative method with a juridical-normative approach based on comparison through literature study techniques supported by interviews. This research shows that there are similarities in the regulation of ownership of medical records in the New Hampshire Statute with Law Number 17 of 2023 and Minister of Health Regulation Number 24 of 2022. Differences in rights to medical records in Law Number 17 of 2023 and Minister of Health Regulation Number 24 of 2022 show that the access rights contained in Law Number 17 of 2023 are an additional right to the ownership right to electronic medical record information in Minister of Health Regulation Number 24 of 2022, which is still in effect today. Abstrak. Ketidakjelasan pada perlindungan hak pasien terhadap rekam medis pada UU No. 17 Tahun 2023 tentang Kesehatan menimbulkan perdebatan untuk mengklaim kepemilikan rekam medis antara pasien dengan fasilitas layanan kesehatan. Penelitian ini membandingkan pengaturan kepemilikan rekam medis sebelum dan sesudah UU No. 17 Tahun 2023 tentang Kesehatan serta hukum internasional seperti Statuta New Hampshire dan HIPAA. Penelitian ini dilakukan dengan tujuan untuk mengetahui dan menganalisis kepemilikan rekam medis menurut UU No. 29 Tahun 2004 dan UU No. 17 Tahun 2023 tentang Kesehatan dengan Statuta New Hampshire, serta mengetahui akibat hukum pasca diberlakukannya UU No. 17 Tahun 2023 tentang Kesehatan atas perlindungan hak pasien atau keluarga terhadap isi rekam medis. Metode analisis penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan yuridis-normatif berdasarkan perbandingan melalui teknik studi pustaka yang ditunjang oleh wawancara. Penelitian ini memberikan hasil bahwa terdapat persamaan pengaturan kepemilikan rekam medis dalam Statuta New Hampshire dengan UU No. 17 Tahun 2023 dan Permenkes No. 24 Tahun 2022. Perbedaan hak terhadap rekam medis dalam UU No. 17 Tahun 2023 dengan Permenkes No. 24 Tahun 2022 menunjukkan bahwa hak akses yang ada pada UU No. 17 Tahun 2023 merupakan hak tambahan dari hak milik atas informasi rekam medis secara elektronik dalam Permenkes No. 24 Tahun 2022 yang keberadaan masih berlaku hingga saat ini.